Application of the modern approach to the adoption of organizational and technological solutions in conditions of dense building and compressed conditions based on the DAD approach. - Chertkov О.; Tsehelnyi, V.; Ermolovich, D.; Plaksiuk, D. (Ways to Improve Construction Efficiency, 2019)
The article deals with the problems of investors (customers) during the establishment of medical institutions. Possible options for the implementation of medical facilities are defined, namely the lease of premises, the purchase of real estate, new construction or the combination of the last two. A real example of the reconstruction of a non-residential building under the medical center is considered and problems identified during the implementation of the construction project are identified. The author defines the DAD approach, the possibilities of its application to increase the reliability of data necessary for the adoption of organizational and technological solutions.